Pengembangan Kualitas Pelayanan Produk Telekomunikasi Selular Diatas Kapal Menggunakan Metode Service Quality & Quality Function Deployment - Maya Arlini Puspasari; Nia Kurniasih (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2013)
The need for telecommunications, including the category of primary need for the people of Indonesia, one of the important aspects that need to be considered by the telecommunications company is a technological innovation that can cover all of Indonesia to outlying places, not only telecommunications on land even when in the middle of the ocean though. With Cellular Telecommunications Company cooperation to support the availability of telemetry, then develop into the greatest benefit is the availability of the Mobile phone network for the passengers on board, to continue to innovate and deliver the best to customers, the service providers must continue to improve quality. Research conducted using the SERVQUAL method to measure the quality of service based on the five dimensions of service quality by analyzing gaps that occurs due to a mismatch between customer expectations and perceptions of the quality of service received. In this study wants and expectations of consumers translated into House of Quality in Quality Function Deployment. Results of research propose using strategy value to get priority repairs according to the company's ability